Rethinking Development Policy : Deindustrialization, Servicification and Structural Transformation - Atolia, Manoj (IMF Working Papers; Working Paper ;, 2018)
This paper takes a fresh look at the current theories of structural transformation and the role of private and public fundamentals in the process. It summarizes some representative past and current experiences of various countries vis-a-vis structural transformation with a focus on the roles of manufacturing, policy, and the international environment in shaping the trajectory of structural transformation. The salient aspects of the current debate on premature deindustrialization and its relation to a middle-income trap are described as they relate to the path of structural transformation. Conclusions are drawn regarding prospective future paths for structural transformation and development policies.